Leonardo Padura Fuentes y su detective Nostálgico - Franken K., Clemens A. (Revista Chilena de Literatura, 2009)
This article places the detective novels by the well known Cuban author Leonardo PaduraFuentes within the general tradition of detective fi ction, as well as within the Cuban tradition. The psychological, social and ideological profi le of the novels' main investigator and protagonist, Mario Conde, are analyzed together with his method of investigation, his relationship with friends, workmates, women and his strong social and cultural criticism. Besides, a special emphasis is placed on the forms of assimilation (polemical of the Cuban detective genre and parodical both of the classic mystery detective genre and the hard-boiled detective fiction) in his hybrid detective novels increasingly moving into a more postmodern detective literature.